2010
DOI: 10.1186/1471-2334-10-344
|View full text |Cite
|
Sign up to set email alerts
|

Blood cultures for the diagnosis of multidrug-resistant and extensively drug-resistant tuberculosis among HIV-infected patients from rural South Africa: a cross-sectional study

Abstract: BackgroundThe yield of mycobacterial blood cultures for multidrug-resistant (MDR) and extensively drug-resistant tuberculosis (XDR-TB) among drug-resistant TB suspects has not been described.MethodsWe performed a retrospective, cross-sectional analysis to determine the yield of mycobacterial blood cultures for MDR-TB and XDR-TB among patients suspected of drug-resistant TB from rural South Africa. Secondary outcomes included risk factors of Mycobacterium tuberculosis bacteremia and the additive yield of mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(24 reference statements)
1
21
1
Order By: Relevance
“…6 It was found that the mean CD 4 count was in increasing pattern without any turn down for three and half years among TB coinfected individuals, but the group which were TB free had fl uctuating mean CD4 count. This shows that there is marked increase in CD4 count in TB co-infected individuals despite lower initial CD4 count before starting ART.…”
Section: Saarc J Tuber Lung Dis Hiv/aids 2013;x(1)mentioning
confidence: 99%
See 1 more Smart Citation
“…6 It was found that the mean CD 4 count was in increasing pattern without any turn down for three and half years among TB coinfected individuals, but the group which were TB free had fl uctuating mean CD4 count. This shows that there is marked increase in CD4 count in TB co-infected individuals despite lower initial CD4 count before starting ART.…”
Section: Saarc J Tuber Lung Dis Hiv/aids 2013;x(1)mentioning
confidence: 99%
“…HIV-infected TB patients have higher rates of extra-pulmonary disease, atypical clinical presentations, and normal chest radiographs. 6 Tuberculosis and HIV control programmes clearly have mutual concerns: the prevention of HIV infection and the treatment of HIV/AIDS should be components of tuberculosis control, and tuberculosis care and prevention should be priorities in the management of HIV/AIDS. 7 TB is the most frequent life-threatening opportunistic disease among people living with HIV and remains a leading cause of mortality, even among persons receiving antiretroviral therapy (ART).…”
Section: Introductionmentioning
confidence: 99%
“…12 Such an approach may be particularly important for the HIV infected patients presenting with significant immunosuppression (as manifest by low CD4 count) that were frequently observed to suffer early death in this cohort. 13 Other HIV-prevalent settings have found early TB death in the form of sepsis and/or mycobacteremia, 14,15 and have suggested that more aggressive anti-TB management should be trialed. Although it was common practice to prescribe antiretrovirals between 2 weeks and 2 months after TB treatment initiation in the antiretroviral naive per international consensus recommendations, 16 four of the seven patients with early death were on antiretrovirals prior to admission.…”
mentioning
confidence: 99%
“…In this cohort, 64% patients with culture confirmed Mtb complex disseminated disease had a CD4 count of <50 cells/mm 3 and 2/3rd of these had a CD count of <25 cells/mm 3 . In a subsequent study in rural South Africa in patients with HIV, diagnosis of MDR/XDR-TB was made by blood culture alone in 12 patients with additive yield for diagnosis of DR-TB suggesting use of mycobacterial blood cultures in all patients suspected of DR-TB in similar settings [42].…”
Section: Way Forwardmentioning
confidence: 99%